Advances in Nature-Inspired Computing and Applications - Shandilya, Shishir Kumar; Shandilya, Smita; Nagar, Atulya K. (EAI/Springer Innovations in Communication and Computing, 2019)
This book contains research contributions from leading global scholars in nature- inspired computing. It includes comprehensive coverage of each respective topic, while also highlighting recent and future trends. The book focuses on the current research while highlighting the empirical results along with theoretical concepts to provide a comprehensive reference for students, researchers, scholars, professionals and practitioners in the field of Advanced Artificial Intelligence, Nature-Inspired Algorithms and Soft Computing. Topics include Hybrid Bio-inspired Computing; Membrane Computing; Krill Herd Algorithm; Stochastic Optimization; Firefly Optimization Algorithm;Artificial Bee Colony Algorithm; Particle Swarm Optimization; Lion Optimization Algorithm; and Monkey Search Optimization. • Presents complete coverage of nature-inspired computing and applications; • Provides a comprehensive, criticaland descriptive examination of all facetsof nature-inspired algorithms and naturally-intelligent machines; • Fundamentals are emphasized throughout the book to provide strong basis for students.